Rare case of a mandibular first molar with seven canals confirmed by cone beam computed tomography and its endodontic management - Vineet, Agrawal; Sonali, Kapoor; Dhwani, Bhesania (International Journal of Health Sciences, 2018)
The endodontic treatment of a mandibular molar with aberrant canal configuration can be diagnostically and clinically challenging. This case report presents the treatment of a mandibular first molar with seven root canals, of which four canals were located in the mesial root and three in distal root. This case presents a rare anatomic configuration and points to the importance of expecting and searching for additional canals.